(untitled) (Research, Society and Development, 2021)
The current pandemic caused by the new coronavirus, has represented one of the most serious public health problems in the world of all time. To cope with COVID-19, several reforms and adaptations in the health sector were necessary to face this disease with high contagion power and with such high numbers of lethalities. The objective of this work was to carry out a bibliographic survey to study how the use of PPE for the safety of health professionals and workers in the pandemic period of COVID-19. One of the main impositions of this new reality was the increased demand for care in health establishments, thus increasing the risk for health professionals and workers to develop infectious diseases such as COVID-19, when compared to the general population, due to greater chance of exposure to viral load during the work period. In diseases such as COVID-19, in addition to droplet transmission and contact, there is exposure to aerosol-generating procedures during care for these patients, and health professionals can act as potential asymptomatic transmitters, infecting other patients, professionals and family members. In this context, personal protective equipment is an effective tool for preventing infection and reducing contagion by COVID-19.